(untitled) (Conference on English Language Teaching, 2025)
The integration of multimedia technology in English language instruction has revolutionized educational methodologies, particularly in higher education. This study employs a Semantic Literature Review to analyze recent advancements and trends in multimedia applications for English language teaching in universities. Drawing data from international publishers, including Scopus, over the last five years (2019–2024), the review identifies key technological innovations, pedagogical strategies, and their impacts on learner engagement and proficiency. Findings reveal that multimedia tools, such as interactive software, video-based learning platforms, and augmented reality, significantly enhance language acquisition by fostering immersive and adaptive learning environments. Furthermore, the study highlights the challenges of implementation, including technological disparities and faculty readiness, and proposes strategies to optimize multimedia integration. This review contributes to the academic discourse by providing a comprehensive synthesis of existing literature and identifying future directions for multimedia-enhanced English language education in higher education.